"Don't Sell Me the Enemy's Literature": A Self-Study of Teaching Literature in Politically Fraught Contexts. Issue 3 (1st September 2016) - Poyas, Yael
Abstract: This article describes a self-study pursuant to a clash between a lecturer and a student concerning the teaching of literature in a politically fraught context. The learning group is composed of Arab and Jewish teachers at a college in northern Israel. The work read by the group expresses a Palestinian perspective. The incident, discussed with reference to the concepts of ethical reading and in-between space, is explained against the background of the lecturer's professional views and the complexity of teaching literature in a polarized and conflicted society. Analysis of the incident, accompanied by a look at the professional literature, reveals the lecturer's blind spots as well as the complexity of the situation in which she was acting. Details of the case and the process of its interpretation may serve to enrich the perspectives of literature teacher educators who believe in ethical reading and in constructing an in-between space in their lessons, providing them with insights regarding teaching in contexts fraught with cultural tensions.